Viscoelastic behavior of chemically fueled supramolecular hydrogels under load and influence of reaction side products - Martin Kretschmer (Nature Portfolio, 2021)
The mechanical properties of out-of-equilibrium, chemically fueled supramolecular materials are largely unexplored. Here, the effect of applied load and the concentration of reaction side products on the viscoelastic properties of chemically fueled supramolecular hydrogels is investigated.